the alternative fine penalty for the deprivation of liberty - داوود صباح سامي; رضا صابرين ابراهيم (Journal of Legal Sciences, 2021)
This current entitled (The Alternative Fine Penalty for the Deprivation of Liberty) addressed and studied this alternative punishment for a short-term prison sentence. We sought through it to search the essence of this alternative punishment by dividing this study into two sections, in the first section we addressed the concept of the alternative fine to the deprivation of liberty, which was divided into two requests, the first request included the definition of the alternative fine penalty for the deprivation of liberty, while the second request discussed the characteristics of the alternative fine penalty for the deprivation of liberty. As to the second section, it tackled the justifications of the alternative fine penalty for the deprivation of liberty, which was divided into three requests, the first request addressed the social and economic justifications, whereas the second request addressed the justifications of the punitive system, and the third request tackled the defects of the traditional criminal fine penalty. Our study ended with a conclusion including a group of conclusions and suggestions.